Efficacy of low-load blood flow restricted resistance EXercise in patients with Knee osteoarthritis scheduled for total knee replacement (EXKnee): protocol for a multicentre randomised controlled trial - Inger Mechlenburg; Per Aagaard; Stian Langgård Jørgensen; Marie Bagger Bohn (BMJ Open)
Introduction Up to 20% of patients undergoing total knee replacement (TKR) surgery report no or suboptimal pain relief after TKR. Moreover, despite chances of recovering to preoperative functional levels, patients receiving TKR have demonstrated persistent deficits in quadriceps strength and functional performance compared with healthy age-matched adults. We intend to examine if low-load blood flow restricted exercise (BFRE) is an effective preoperative method to increase functional capacity, lower limb muscle strength and self-reported outcomes after TKR. In addition, the study aims to investigate to which extent preoperative BFRE will protect against surgery-related atrophy 3 months after TKR.Methods In this multicentre, randomised controlled and assessor blinded trial, 84 patients scheduled for TKR will be randomised to receive usual care and 8 weeks of preoperative BFRE or to follow usual care-only. Data will be collected before randomisation, 3–4 days prior to TKR, 6 weeks, 3 months and 12 months after TKR. Primary outcome will be the change in 30 s chair stand test from baseline to 3-month follow-up. Key secondary outcomes will be timed up and go, 40 me fast-paced walk test, isometric knee extensor and flexor strength, patient-reported outcome and selected myofiber properties.Intention-to-treat principle and per-protocol analyses will be conducted. A one-way analysis of variance model will be used to analyse between group mean changes. Preintervention-to-postintervention comparisons will be analysed using a mixed linear model. Also, paired Student’s t-test will be performed to gain insight into the potential pretraining-to-post-training differences within the respective training or control groups and regression analysis will be used for analysation of associations between selected outcomes.Ethical approval The trial has been accepted by the Central Denmark Region Committee on Biomedical Research Ethics (Journal No 10-72-19-19) and the Danish Data Protection Agency (Journal No 652164). All results will be published in international peer-reviewed scientific journals regardless of positive, negative or inconclusive results.Trial registration number NCT04081493.